An Analysis of Figurative Language in William Shakespeare’s Sonnets - Annisafitri , Advenda Gantaruni; Ekawati, Anita Dewi (Institut Agama Islam Negeri Palopo, 2025)
This research explores the use of figurative language in William Shakespeare's sonnets through an analysis. In this study, there is a comprehensive analysis of six selected sonnets, namely: Sonnet 127, Sonnet 130, Sonnet 131, Sonnet 132, Sonnet 133, and Sonnet 139. The purpose of this study is to explore how figurative language is used in William Shakespeare's sonnets by using Perrine's theory and to reveal the techniques used by Shakespeare to enrich his poems. The research method used was descriptive qualitative, identifying and categorizing 53 examples of figurative language in the selected sonnets. The technique of data collection is by reading the sonnets thoroughly, noting in detail the figurative language present and connecting with the theory. Ten of Perrine's twelve theories were found, namely simile, metaphor, personification, synecdoche, metonymy, symbol, hyperbole, irony, paradox, and apostrophe. The findings of this study show the dominant use of metaphor and personification, complemented using synecdoche, metonymy, hyperbole, and other devices. The way Shakespeare uses figurative language makes his poems seem more vivid and evokes deep emotions, especially for the readers. Shakespeare's poetry and figurative language have an enduring power in literature and offer valuable insights to be analyzed more deeply.